THE PERSPECTIVE OF PLURALISTIC SOCIETY ON THE TRANSFORMATION OF INTELLECTUAL PROPERTY PROTECTION IN THE DIGITAL ERA AS AN EFFORT TO PREVENT COPYRIGHT INFRINGEMENT - Bratajaya, Maria Magdalena Astrina; Hoesein, Zainal Arifin (Ridwan Institute, 2024)
In the digital era, intellectual property rights (IPR) face unprecedented challenges due to rapid technological advancements and the global accessibility of digital content. This study examines the impact of digital developments on copyright infringement in Indonesia, a diverse and pluralistic society, and analyzes effective legal approaches for copyright protection within its unique socio-cultural context. Employing a normative-juridical approach, the research explores existing legal frameworks, including Indonesia’s Copyright Law and the Electronic Information and Transaction Law, to assess their capacity to address issues related to digital copyright infringement and the role of artificial intelligence (AI) in both enforcing and infringing copyright. By analyzing relevant statutes and applying a conceptual approach, the study evaluates the extent to which current legal mechanisms support creators' rights while balancing cultural values. The findings reveal that Indonesia’s legal framework requires adaptive and culturally relevant modifications to effectively protect copyright in a digitally connected, multicultural society. This research contributes to the discourse on digital copyright law, emphasizing the need for flexible regulations and collaborative efforts among government, communities, and stakeholders to foster compliance and awareness. Future research is recommended to focus on adaptive regulatory models that integrate technology with IPR protection and explore international cooperation to address the global challenges of digital copyright.